Design and Characterization of a Novel Rotating Corrugated Drum Reactor for Wastewater Treatment - Sarah M. Meunier; Joanne Gamage; Zdravko Duvnjak; Zisheng Zhang (International Journal of Photoenergy)
A novel photoreactor system consisting of a TiO2-coated corrugated drum and a UV light source is experimentally characterized for the treatment of phenol-polluted wastewaters. The design incorporates periodic illumination and increased agitation through the introduction of rotation. The effects ofrent degrees and flat fins to increase surface area, varying rotational speed, initial pollutant concentration, and illumination intensities were studied. The corrugated and finned drums did not exhibit a critical rotational speed, indicating that there is excellent mass transfer in the system. A Langmuir-Hinshelwood kinetic analysis was applied to the degradation, and an average adsorption coefficient of K=0.120 L/mg was observed. The overall reaction rate increased with increasing surface area from 0.046 mg/L/min for the annular drum to 0.16 mg/L/min for the 40-fin drum. The apparent photonic efficiency was found to increase with increasing surface area at a faster rate for the corrugations than for the fin additions. The energy efficiency (EE/O) found for the drums varied from 380–550 kWh/m3, which is up to 490% more energy-efficient than the annular drum.